Testing a Social Innovation in Financial Aid for Low-Income Students: Experimental Evidence from Italy - Davide Azzolini; Alberto Martini; Enrico Rettore; Barbara Romano; Antonio Schizzerotto; Loris Vergolini (Institute of Labor Economics (IZA), 2018)
This paper presents the results of a randomized controlled trial aimed at testing the effectiveness of an innovative intervention of asset building (Percorsi) on high school students' transition to the university. Contrary to most traditional forms of financial aid, the tested intervention is expected to enhance an active involvement of the families and imposes a strong conditionality in the use of the benefits. The experiment, called ACHAB (Affording College with the Help of Asset Building) has been carried out in the province of Torino (Northwest Italy) between 2014 and 2017. For the evaluation purpose, an ad hoc survey has been carried out to collect longitudinal information on enrolment decisions and academic performances (number of exams and persistence) during the first semester and at the beginning of the second year. External data and applicant baseline information were used to perform a multidimensional targeting strategy aimed at identifying the 'target population', i.e. those students who were at risk of giving up their university enrolment decisions because of economic reasons. The experimental results point to the existence of positive and significant effects of the program on university enrolment and sizeable and significant positive effects on academic performance and university persistence. The effects of the program are significantly larger for students coming from vocational schools than for students who completed technical or general secondary schools.
Keywords: C90; D04; I22; I24; 330; higher education; social inequality; financial aid; asset building; randomized controlled trial